Succeeding Through People: An Overview of How Business Excellence Practices Have Changed the HR Landscape - Jayaraman, R. (Prabandhan: Indian Journal of Management, 2013)
In the last 60 years, HR practices have undergone many changes. Driven by business conditions and advancements in technology, people practices have helped in steep improvements in productivity and value creation. Since the advent of TQM in Japan in 1950, kicked off by the visit of Dr. W. Edwards Deming, the HR ethos have moved from the days of "Time and Motion Study" of Frederick Taylor to Quality Circles and beyond, where the philosophy has been one of "Continuous Improvement leading ultimately to Personal Growth and Self Realization". The Business Excellence (BE) movement, which was started in the USA in 1987 through the declaration of the Malcolm Baldrige National Quality Award (MBNQA) for excellently performing US companies, was a logical extension of the TQM wave that swept Japan and other countries. The MBNQA was followed by several BE models, like European Foundation for Quality Management (EFQM). Building on the key concepts of TQM, such as Plan, Do, Check, Act (PDCA) , the BE models set the tone for a holistic look at managing companies through systematic process deployment. People practices came in for their share of scrutiny and large-scale improvements. This paper highlights the areas where the BE wave has impacted Human Resources (HR) and people practices. It also deals with the differences between the TQM and the BE ways of embracing the HR function to align people workings with the rest of the company requirements, thereby providing the methodologies to ensure that people remain at the centre of the excellence drive by companies in an increasingly competitive world. The paper also tracks the more recent developments, such as the growth of the service industry and the need for the BE movement to deal with this major change in a more focused manner.